PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 7E DENGAN TEKNIK MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VIII.5 SMP NEGERI 5 PEKANBARU - Hardiana, Wan; Arnentis, Arnentis; Syafi’i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aimed to improve Student’achievement of students in class VIII.5 of SMP Negeri 5 Pekanbaru by implementation Learning Cycle 7E model with Mind Mapping technique. It was done in SMP Negeri 5 Pekanbaru on Maret of Mei 2019. Parameters which measure were student’s achievement. The methods of this research was classroom action research by implementation Learning Cycle 7E model with Mind Mapping technique. It was done in two cylce. There were planning step, acting step, observation step and reflection step for each cycle. The first cycle to apply learning materials KD.3.10. about the excreation system and in the second cycle to apply learning materials KD.3.11. regarding the concepts of vibrations, waves and sounds. The research instrument used was a learning device that consist of a lesson plan, syllabus, assesment authentic sheet, observation shee.t The collected data was analysed descriptively. The result of this research showed that Student’achievement in the first cycle was 79,2 with a predicate (C) and increased in the second cycle up to 89,93 with a predicate (B). Completeness percentage in the first cycle was 42,85% and increased in the second cycle up to 71,42%. Student’s attitude in the first cycle was 71,02 with a predicate (D) and increased in the second cycle up to 86,92 with a predicate (B). It can be conclude that Learning Cycle 7E model with Mind Mapping technique can improve Student’achievement of student in class VIII.5 SMP Negeri 5 Pekanbaru.Key Words: Learning Cycle 7E, Student’ Achievement, Mind Mapping Technique